DEVELOPMENT OF INVESTMENT STRATEGIES FOR AGRI-FOOD ENTERPRISES - Демчук, Н. І. (Scientific Progress & Innovations, 2014)
It has been determined that the investment activities and its strategic planning must take a leading place in the socio-economic activities and the development of food enterprises in general terms by the action of uncertainties and cyclical financial crises. This is needed to find sources of investment finance companies to maintain or improve their competitiveness, investment restructuring provision as a factor of improving the efficiency, modernization and development of new product samples as a response to the demands and challenges of the external and internal environment of the food market. Investment activity is the key for solving environmental problems and socio-economic problems that accompany the development of the food industry. Investments are needed to improve the quality of products, its standardization and certification.